OP0175 IDENTIFYING PERIPHERAL VASCULAR MONOSODIUM URATE CRYSTAL DEPOSITION WITH DUAL-ENERGY CT: FACT OR FICTION? THE VASCURATE STUDY. (2nd June 2020) - Pascart, T.; Carpentier, P.; Norberciak, L.; Legrand, J.; Houvenagel, E.; Becce, F.; Budzik, J. F.
Abstract : Background: The close relationship between gout and cardiovascular diseases is well established. A growing hypothesis explaining this association would be that monosodium urate (MSU) crystals are deposited within vessel walls. Dual-energy computed tomography (DECT) can identify and quantify MSU crystal deposition in soft tissues. It remains unclear whether vascular spots exhibiting DECT attenuation characteristics of MSU are artefacts or true MSU crystal deposits. Objectives: The objectives of this study were to determine whether the presence of peripheral vascular MSU crystal deposition identified with DECT is associated with the extent of MSU deposits in joint soft tissues, and if this association persists over time under urate-lowering therapy. Methods: Patients with a clinical suspicion or established gout diagnosis prospectively underwent DECT for identification and quantification of the MSU crystal burden in their knees and feet. Some of these patients were also enrolled in the GOUT-DECTUS longitudinal study, and thus underwent follow-up DECT scans of their knees and feet at 6, 12 and 24 months. DECT scans were examined for the presence of vascular spots ≥0.01 cm3 classified as MSU crystal deposits according to the default post-processing settings. Multiple linear regressions adjusting on serum urate levels and gout diagnosis were implemented to determine the association between DECT MSU crystal volume in joint soft tissues, and the presence of vascular MSU deposits. Mixed linear models were used to compare DECT volumes of MSU crystal deposition in soft tissues between vascular MSU positive and negative patients during follow-up. Results: A total of 169 patients were included, of which 140 had a final diagnosis of gout, including 15 also included in the longitudinal study. Patients were mostly male (78.8%) and were 65.5 ± 14.6 years old. Among gout patients, disease duration was 9.3 ± 9.9 years and 56.5% were urate lowering therapy-naive. A total of 11/29 (37.9%) controls and 40/140 (28.6%) gout patients presented with a least one vascular spot of DECT MSU deposition, with an average volume of 0.02 ± 0.02 cm3, and all subjects also presented at least one vascular calcification. In the feet, patients positive for vascular DECT MSU crystal deposition had an MSU volume of 3.81 ± 10.06 cm3 in joint soft tissues, compared with 1.85 ± 7.72 cm3 for those without vascular MSU deposition (p=0.018). In the knees, patients with vascular MSU deposition had an MSU crystal volume of 6.03 ± 24.13 cm3 in joint soft tissues, compared with 0.83 ± 2.88 cm3 for those without vascular evidence of MSU deposition. In the longitudinal subgroup analysis, coefficients of the fixed effects for the presence of vascular MSU deposits on the MSU crystal volume in joint soft tissues was 0.4 (p=0.35) in the feet and 1.21 (p=0.03) in the knees. The presence of vascular DECT MSU deposits was associated with a 3.4-fold increase in MSU crystal volume in knee joint soft tissues throughout follow-up. Conclusion: This study suggests that some vascular spots identified with DECT as MSU crystal deposition may be real and not artefacts. This correlation remains throughout follow-up in the knees. However, the comparable prevalence of vascular DECT MSU deposits between gout patients and controls, the systematic co-existence of vascular calcifications and the uneven regression under urate-lowering therapy requires further analysis to determine which DECT spots are artefacts and which are not. References: [1]Dual-Energy Computed Tomography Detection of Cardiovascular Monosodium Urate Deposits in Patients With Gout. Klauser AS, Halpern EJ, Strobl S, Gruber J, Feuchtner G, Bellmann-Weiler R, Weiss G, Stofferin H, Jaschke W. Disclosure of Interests: Tristan Pascart Grant/research support from: Research Grant Horizon Pharma, Consultant of: Novartis, BMS, Sanofi, Pfizer, , Speakers bureau: Novartis, BMS, Paul Carpentier: None declared, Laurène Norberciak: None declared, Julie Legrand: None declared, Eric Houvenagel Speakers bureau: Janssen, Novartis, Fabio Becce: None declared, Jean-François Budzik: None declared